Optimization of Intercropping Corn in Immature Oil Palm Plantations (Non-Yielding Stage) - Cecep Ijang Wahyudin; Rannando Rannando; Fachri Ibrahim Nasution (Fakultas Teknologi Pertanian Unsultra, 2026)
The optimization of land use in immature oil palm plantations (non-yielding stage) is crucial to enhancing productivity and supporting sustainable agriculture. This study aimed to evaluate the effect of corn intercropping systems on vegetative growth, yield, and land-use efficiency in immature oil palm plantations. An experimental method with a Randomized Block Design was employed, consisting of two treatments: corn monoculture (control) and corn intercropped in the inter-row spaces of immature oil palms, each replicated three times. Observed parameters included plant height, number of leaves, cob weight, grain yield, and Land Equivalent Ratio (LER). The results demonstrated that intercropped corn exhibited higher vegetative growth, including increased plant height and leaf number, due to optimal utilization of growing space and improved microclimatic conditions, such as stable soil moisture and light shading. Generative growth also improved, as evidenced by higher cob weight and grain yield, which reached 7.6 t/ha compared to 6.9 t/ha in monoculture. The LER value of 1.10 indicated a 10% higher land-use efficiency in intercropping systems. Positive interactions among crops minimized competition for nutrients and water, enhanced weed control, and maintained stable microclimatic conditions, contributing to sustainable plantation management. Economically, intercropping provided additional income for farmers during the immature phase of oil palms without compromising the main crop. In conclusion, corn intercropping in immature oil palm plantations optimizes space, improves both vegetative and generative growth, enhances yield per unit area, increases LER, and offers ecological and economic benefits, making it a viable and sustainable strategy for maximizing productivity and supporting diversified agricultural systems.